2021
DOI: 10.3389/fnut.2021.754663
|View full text |Cite
|
Sign up to set email alerts
|

Processed Food and Atopic Dermatitis: A Pooled Analysis of Three Cross-Sectional Studies in Chinese Adults

Abstract: Objective: The effect of processed foods on atopic dermatitis (AD) in adults is unclear. This study was to evaluate the association between processed foods and AD in the Chinese adult population.Design: This study included three population-based cross-sectional studies using cluster sampling by villages, institutions, or factories. Participants underwent dermatological examinations by certificated dermatologists and a food frequency questionnaire survey. A spot urine sample was collected to estimate the daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This study used MR analysis methods and did not find a causal relationship between vegetable intake or fruit intake and AD. Notably, previous studies have shown that the consumption of meat (48) , wheat (48) , processed foods (49,50) and coffee is associated with the onset of AD (51) . In contrast, our study did not find a causal relationship between the above factors.…”
Section: Discussionmentioning
confidence: 99%
“…This study used MR analysis methods and did not find a causal relationship between vegetable intake or fruit intake and AD. Notably, previous studies have shown that the consumption of meat (48) , wheat (48) , processed foods (49,50) and coffee is associated with the onset of AD (51) . In contrast, our study did not find a causal relationship between the above factors.…”
Section: Discussionmentioning
confidence: 99%
“…An online questionnaire survey was used to collect data on participants’ socioeconomic status (annual household income) and lifestyle characteristics (physical activity, second‐hand smoke exposure, alcohol consumption, parental education level, and intake of red meat, white meat, and fish). 28 , 29 Demographic information on age, sex, race, weight, height, and history of hypertension in participants was collected by investigators during the health examination. Weight divided by height squared (kg/m 2 ) was used to compute the body mass index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…A low nutritional state has been associated with lower gut microbiome diversity, alterations of which have been hypothesized to be triggers for immunological disease 4 . Similarly, consumption of any processed food (>1/week) has been associated with an increased risk for developing atopic dermatitis 5 . Additionally, diets deficient in micronutrients have been associated with alopecia 3 .…”
Section: Food Insecure Food Securementioning
confidence: 99%